Ferulic acid reduces GLP‐1 degradation to ameliorate diet‐induced obesity‐associated hepatic steatosis - Yuxuan An; Lichao Zhang; Xiaxia Fan; Kaili Cui; Shuiling He; Pengyu Ji; Jinmiao Tian; Zhuoyu Li (Food Frontiers, 2024)
Abstract GLP‐1 is a vital candidate for stimulating insulin secretion in a glucose‐dependent manner, reducing body weight and eliminating nonalcoholic fatty liver disease with few side effects. Therefore, elevating GLP‐1 secretion and antagonizing the enzymatic cleavage by DPP4 are the main direction of GLP‐1‐based drug development. The present study implies that ferulic acid (FA) treatment increased the serum GLP‐1 level in diet‐induced obesity mice. The binding of FA to GLP‐1 effectively prevented the enzymatic cleavage of GLP‐1 by DPP4, which led to the effective elimination of hepatic cellular lipids by GLP‐1 in vitro. Furthermore, studies of fluorescence titration and molecular simulation showed that the combination ratio of FA and GLP‐1 was 1:1, and FA could enhance the stability of GLP‐1 through van der Waals force and electrostatic force binding to GLP‐1. In turn, it increased the level of endogenous GLP‐1. More importantly, data from mass spectrometry analysis revealed that FA bound to GLN‐17, ALA‐18, or ALA‐19 sites of GLP‐1 differently. In addition, after binding to FA, the α‐helix in GLP‐1 did not change significantly, and the biological activity of GLP‐1 was unaffected. These results highlight that FA‐rich food, such as millet and oats, is an excellent source of dietary intervention for metabolic disorders.